Direct Application of Research Study Findings in a Practitioner Setting: The Application of the Small Retail Facilities Model for Retail Facility Assessment - Aboulola, Omar I. (Journal of Marketing Development and Competitiveness, 2018)
Strategic planners and decision makers need a usable and simple software that simplifies and supports their spatial location decision making. They need an artifact (website) that can offer visual representations of current and proposed locations while accounting for demographic, retail location, and social media factors with the use of a regression model that shows the expected annual sales for each potential location selected. 50 users reviewed such software; Users completed 10 questions of SUS and 10 questions of UE. Users reported favorably regarding usability and reported being satisfied with the website overall.